Penguatan Pengaruh Modal Bank Terhadap Pertumbuhan Kredit Melalui Pengelolaan Likuiditas - Ahmad Aziz Putra Pratama (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2019)
The purpose of this research is to examine the effect of bank capital on lending growth with moderation of liquidity level of banking companies listed in Indonesian Stock Exchange. This study used multiple linear regression model and Moderated Regression Analysis (MRA). Data obtained from the company's financial report published in 2010-2016 period. Dependent variable in this research is lending growth proxied with Net Loans Growth. Independent variable used bank capital proxied with Capital Adequacy Ratio (CAR). Moderating variable in this research used liquidity level proxied with liquidity ratio. In addition, controlling variables in this study are firm size proxied with logarithm of total assets and credit quality proxied with Non Performing Loan (NPL). The results showed that bank capital has significant positive effect on lending growth, while the liquidity ratio strengthens positive influence of bank capital on lending growth. Size control variable has significant positive effect on lending growth while NPL variable has no significant effect on lending growth.